2018
DOI: 10.1177/1687814018808684
|View full text |Cite
|
Sign up to set email alerts
|

Cold cranking viscosity of used synthetic oils originating from vehicles operated under similar driving conditions

Abstract: This article assesses the performance and reduction level of five engine oils available from various manufacturers. The trend and intensity of the cranking viscosity changes as measured in the cold cranking simulator were thoroughly analysed. In the presented experiment, alterations in engine oils appearing during actual operation were noted. The tests were conducted under conditions which can be depicted as 'harsh', that is, multiplied starting of the engine, extended engine idling and short stretch driving. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition to the comparison of the viscosity parameters provided by the manufacturers or resulting from the SAE J300 standard with the values from laboratory tests, it was also decided to explore the KV behavior at the sub-zero and above 100 • C. The kinematic viscosity measured at −20 • C is indirectly related to another very important parameter-structural viscosity (measured in the CCS apparatus-Cold Cranking Simulator), which determines engine starting ability at low temperatures [16,28]. A lower value of such viscosity corresponds to an easier start of the engine at low temperatures and means less load being put on the car battery.…”
Section: Kinematic Viscosity At −20 • C and 130 • Cmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the comparison of the viscosity parameters provided by the manufacturers or resulting from the SAE J300 standard with the values from laboratory tests, it was also decided to explore the KV behavior at the sub-zero and above 100 • C. The kinematic viscosity measured at −20 • C is indirectly related to another very important parameter-structural viscosity (measured in the CCS apparatus-Cold Cranking Simulator), which determines engine starting ability at low temperatures [16,28]. A lower value of such viscosity corresponds to an easier start of the engine at low temperatures and means less load being put on the car battery.…”
Section: Kinematic Viscosity At −20 • C and 130 • Cmentioning
confidence: 99%
“…The result for sample #36 is particularly worrying. The research carried out by the authors previously [16] showed that in −30 • C, too high kinematic viscosities may indicate not meeting the requirements of SAE J300 classification in sub-zero temperature parameters (CCS). As a result, it was decided that CCS measurements should be performed for two extreme samples (#13 and #36).…”
Section: Kinematic Viscosity At −20 • C and 130 • Cmentioning
confidence: 99%
See 1 more Smart Citation